Regeneration and Characterization of cultivated and wild cereal genetic resources at ICARDA - Tsivelikas, Athanasios; Kehel, Zakaria (2023)
Seed regeneration is the process that leads to the generation of a new seed-lot for a given accession with the intention to increase its stored seeds in the collection (also called “multiplication”) or to increase the viability of its seeds equal to or above an agreed minimum level, which is referred to as the regeneration threshold. The latter case is often termed as “seed rejuvenation”. Characterization is the description of plant germplasm through recording the expression of highly heritable characters (not affected by the environment) ranging from morphological, physiological or agronomical features to seed proteins and oil or molecular markers (FAO, 2013). This activity provides information on traits that allows discrimination among accessions and facilitates the verification of identity. It also includes the taxonomic identification and verification when needed. The Genebanks of ICARDA conserve “in-trust” a total of 76,730 accessions of small-grained cereals belonging to 68 different taxa and originating from 110 countries (last update December 2021). The term “small-grained cereals” includes cultivated bread wheat (Triticum aestivum L.) and durum wheat (T. turgidum Desf.), primitive tetraploid (e.g. T. dicoccon Schrank) and hexaploid wheat (e.g. T. spelta L.), barley (Hordeum vulgare L.) and their wild relatives (Aegilops, Triticum and Hordeum). It also includes accessions of triticale (x Triticosecale spp.), rye (Secale spp.) and oat (Avena spp). With the exception of rye and some crop wild relatives (e.g. Aegilops speltoides, Aegilops caudata, Hordeum bulbosum) these cereals are self-pollinated, annual and cool-season grasses. The cultivated forms are grown for human food consumption, animal feed and forage. All of these species are found as both, winter and facultative types (growing primarily during the winter months, requiring vernalization to flower, and with ability to withstand prolonged periods of below freezing temperatures) and spring types (growing primarily during the spring and summer months, normally not requiring vernalization to flower). Details on reproductive system (self vs. cross pollination, self-incompatibility) and on growth cycle (annual, biennial, perennial) for the most representative small-grained cereal species maintained by ICARDA’s Genebanks are given in Annex 1. An essential element of seed regeneration is the maintenance of genetic integrity of the original sample. The two concerns are maintaining the occurrence of different alleles and maintaining the frequency of these alleles. Therefore, knowledge on reproductive system, growth cycle and growth habit of an accession are key elements for regeneration process. Cereal accessions at ICARDA are regenerated when seed quantity falls below 1,500 seeds in medium-term storage or when seed viability drops below 85% of initial viability of the stored seeds (75% in case of wild relative species). Regeneration is also undertaken for the newly introduced, collected or received accessions to allow to conduct characterization and multiply seeds to replenish active and base collection and to send samples for safety duplication. Planting of cereals accessions for regeneration at ICARDA is done in the months of November and December to exploit favorable winter season precipitations and to meet the vernalization requirements for the winter type accessions. Characterization can be carried out at any stage of the conservation process, as long as there are sufficient numbers of seeds to sample. However, characterization of accessions at the field is done as soon as the accession will be acquired by ICARDA’s Genebank and is often combined with the regeneration process. The GRS aims to regenerate and characterize the accessions under conditions that meet recognized international standards based on current technologies and scientific knowledge. The purpose of this SOP is to give detailed instructions and to ensure consistency on the regeneration and characterization activities of cultivated and wild cereal germplasm maintained at ICARDA’s Genebank in compliance with national and international treaties and conventions.